Crisis-induced career reflections: post-pandemic career choices of hotel employees - Abd Patah, Mohd Onn Rashdi; Wan Abdullah, Wan Arnidawati; Abdul Majid, Mohd Aliff; Wan Salman, Wan Ahmad Nasroun (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The widespread effects of the COVID-19 pandemic on hotel workforce have been recognized globally. Substantial research on furloughed hotel employees’ jobs and welfare has been reported, but little has been done to examine their career change intention. This study investigated the impact of the COVID-19 pandemic on career change intentions and choices among front-line hotel employees. Utilizing a qualitative approach, the research involved focus group discussions with 10 diverse participants from Kuala Lumpur hotels. Thematic analysis of the data revealed key insights into participants’ experiences and perspectives. The study found that career adaptability, emotional resilience, and supportive organizational environments were crucial in navigating the crisis. Additionally, the pandemic prompted significant career reflection, resulting in some employees considering moving to more stable industries. The study highlights hospitality organizations’ role in fostering adaptability, support mechanisms, and career development opportunities to enhance employee retention and resilience. The originality of the study lies in its focus on the nuanced experiences of front-line hotel staff during a global crisis, providing valuable implications for workforce development strategies in the hospitality sector.